Traffic Offloading in LTE System Based Heteroge- neous Networks - Mosleh, Mahmood F. (Iraqi Journal for Electrical and Electronic Engineering, 2018)
The continuous growing developments in the traffic of mobile data limits the data throughput and capacity of cellular networks. “Heterogeneous Networks (HetNets)” are efficient solution to realize such demands. However, in HetNets, the congestion on the overloaded cellular network can be increased when the traffic of data is pushed from a cellular network to the Wi-Fi. In practice, offloading the cellular data traffic to a Wireless Local Area Network (WLAN) depending on the signal quality is a broadly deployed method to solve such problem. The use of Device to Device (D2D) communication further enhances the traffic offloading in WLAN systems and helps to obtain better throughput, end-to-end delay and network load. However, the critical offloading potential and its impacts on the whole performance is not totally understood. In this paper, the offloading of Long Term Evolution (LTE) traffic is presented using a WLAN for voice and video applications. A comparison is performed among two WLAN mecha- nisms; Distributed coordination function (DCF) and Point Coordination Function (PCF). As well, the effect of add- ing a D2D technology to the PCF is discussed. The WLAN effectively offloaded nodes at their Signal to Interference and Noise Ratio (SINR) becomes more than a specific threshold. Results presented that the PCF mechanism outper- forms the DCF one in terms of packet loss ratio, throughput and the maximum load of the entire network. In addi- tion, the use of a D2D serviced in the PCF helps in further reduction in the network load.